A Systematic Review and Meta-Analysis of the Efficacy and Safety of Tamsulosin Plus Tadalafil Compared With Tamsulosin Alone in Treating Males With Lower Urinary Tract Symptoms Secondary to Benign Prostrate Hyperplasia. Issue 1 (February 2023) - Zhou, Rui; Che, Xuanyan; Zhou, Zhongbao; Ma, Yue
Lower urinary tract symptoms (LUTS) secondary to benign prostrate hyperplasia (BPH) are common geriatric diseases, and its incidence rises with age. The treatment of BPH and LUTS is becoming a burden for health care. The meta-analysis was performed to evaluate the efficacy and safety of combination therapy (tamsulosin plus tadalafil) compared with tamsulosin alone in treatment of males with LUTS/BPH. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses were utilized to conduct this study. There were several databases available for literature retrieval, including Medline, Embase, PubMed, Scopus, Web of Science databases, and Cochrane Controlled Trials Register. To improve the comprehensiveness of the search, related references were also searched. Finally, six randomized controlled trials including 441 patients were included. The combination therapy had significant improvements in total International Prostate Symptom Score ( p < .0001), quality of life score ( p = .003), maximum urine flow rate ( p < .00001), and International Index of Erectile Function ( p < .00001) compared with the tamsulosin monotherapy, but there was no obvious difference in postvoid residual volume ( p = .06). In terms of safety, the combination group had comparable rates of discontinuation due to adverse events ( p = .19) than the monotherapy group except for pain symptoms ( p < .0001). The combination of tamsulosin and tadalafil provided a preferable therapeutic effect compared with the tamsulosin alone in treating males with BPH/LUTS, and both therapy regimens were well tolerated by the patients.